Ageism Attitudes Of Nursing School Students Regarding Older Adults In Sharkia Governorate (Journal of Pharmaceutical Negative Results, 2023)
Background: Ageism and positive self-perceptions of aging are associated with higher levels of well-being, and better health. The aim of the study was to assess ageism attitudes of nursing school students regarding older adults in Sharkia Governorate. Study Design: A descriptive, cross-sectional design was used to conduct this study and to achieve the aim of this study. Setting: The study was conducted at four nursing schools (Tulrak, Fakous, Awlad Saker and Kafer Saker) in Sharkia Governorate from seventeen nursing schools. Subjects: Two hundred nursing school students were selected by using random sample from selected settings. Tools of data collection: Two tools were used to collect data they were: Self-administered questionnaire, socio-demographic characteristic of the nursing school students and Ageism Attitudes Scale (AAS). Results: 36.5% of the nursing school students` fathers and mothers had secondary education. As well, 77.5% of the students had negative ageism attitudes regarding older adults. Conclusion: More than three quarters of the nursing school students had negative ageism attitude regarding older adults. Recommendations: Increase in clinical settings for Gerontological practice in order to give a chance for nursing school students to be more contact with care for an older adults, and Further studies especially qualitative ones should be conducted to explore factors that influence ageism attitude of nursing school students towards the older adults.